V2X Technology in Metro trains using Internet of Things (IOT) and Automatic Train Supervision (ATS) for smart cities - Viswanathan, Vidya; Theresal, T.; Dhanapal, S. (IJRDO -Journal of Computer Science Engineering, 2017)
The concept of intelligent transportation system (ITS) will be built on the foundation of vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) technology. The system will ensure communication between vehicles and the infrastructure. This technology introduces radiobased systems that can see “beyond the sensors” range to augment the information provided by the vehicles advanced driver assist systems (ADAS). This collection of technology marks a new era in vehicle communication. The metro trains operate through Automatic Train Supervision (ATS). The system has the capability to supervise and organize the train movements continuously in an optimum manner. The main function of ATS system is automatic management of train movement with due interfacing with the Automatic Train Protection (ATP)/Automatic Train Operation (ATO)/ Computer Based Interlocking (CBI) systems for automatic route setting and train regulation. The whole idea of interfacing V2X technology with the centralized ATS using IOT is to create opportunities to mine the accumulated data to provide new services by applying intelligent analytics.